2016
DOI: 10.1007/s13277-016-4858-8
|View full text |Cite
|
Sign up to set email alerts
|

Critical role for the long non-coding RNA AFAP1-AS1 in the proliferation and metastasis of hepatocellular carcinoma

Abstract: Increasing evidence has indicated that dysregulation of long non-coding RNAs (lncRNAs) can contribute to the progression and metastasis of human cancer, including HCC. Previous studies have shown that the lncRNA AFAP1-AS1 plays a critical role in cancer. However, the roles of AFAP1-AS1 in HCC remain to be determined. In the present study, AFAP1-AS1 was found to be increased in HCC tissues, and high AFAP1-AS1 expression was associated with tumor size, TNM stage, vascular invasion, and poor prognosis. Silencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…30,35,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] In this review, the related clinicopathological characteristics and molecular functions of this lncRNA in cancers are presented in Tables 1 and 2.…”
Section: Identification Of Afap1-as1mentioning
confidence: 99%
“…30,35,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] In this review, the related clinicopathological characteristics and molecular functions of this lncRNA in cancers are presented in Tables 1 and 2.…”
Section: Identification Of Afap1-as1mentioning
confidence: 99%
“…Recent studies have shown that AFAP1-AS1 promoted cells proliferation and invasion in nasopharyngeal carcinoma, hepatocellular carcinoma, esophageal squamous cell carcinoma, gallbladder cancer [17, 19, 22, 23]. To investigate roles played by AFAP1-AS1 in CCA, we first examined the expression of AFAP1-AS1 in all 4 CCA cell lines (QBC939, CCLP1, HuCC-T1 and RBE) and the nonmalignant cholangiocyte cell line BEC.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed procedure was performed as our previous described [19]. In brief, total RNA was extracted from cells using Trizol Reagent (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations